Developing a Framework to Increase Access to Mental Health Services for Children With Special Needs in Ethiopia - Hughes, Tammy L.; Quinn, Cydney; Tiberi, Amy; Zeleke, Waganesh A. (Frontiers in Sociology, 2020)
The availability and accessibility of Westernized mental health diagnostic processes and evidence-based treatments are limited in developing countries, such as Ethiopia (Kakuma et al., 2011; Hohenshil et al., 2013; Wondie, 2014; Zeleke et al., 2017b). Similar to other developing nations, there is (a) a lack of health care services for mental practices to build on, (b) limited services that are well-suited to the culture (Wondie, 2014; Zeleke et al., 2019), (c) limited scientific literature useful for documenting the needs of the Ethiopian public, and (d) too few mental health professional preparation programs (Zeleke et al., 2019). Whereas Western cultures generally follow the biomedical model conceptualization and treatment of disease, non-Western cultures, such as Ethiopia tend to adhere to traditional and religious views to explain the origin of mental illness (Kortmann, 1987; Jacobsson and Merdassa, 1991). Mental health symptoms may be attributed to supernatural causes or other spiritual crises, rather than a combination of biopsychosocial influences. As such, individuals seeking help with mental health symptoms in Ethiopia are mostly limited to family, friends and local community healers (Zeleke et al., 2017a, 2019). When individuals are brought to the few places providing Westernized mental health care, it is often only after exhausting other traditional and religious alternatives (Bekele et al., 2000). Even when there is a desire to seek Westernized services, socioeconomic circumstance, cultural factors (e.g., a focus on collectivism practices), negative attitudes toward mental illness, along with unfamiliarity and fear of these new practices, are noted barriers to receiving treatments. Beliefs passed down through cultural taboos go on to effect multiple generations. Not only do barriers affect individuals, but they also negatively impact the range of services for children, families and communities. With the ultimate goal of improving mental health care access for children, a full appreciation of the context is essential.